Denitrification is the major nitrous acid production pathway in boreal agricultural soils - Bhattarai, Hem Raj; Wanek, Wolfgang; Siljanen, Henri M. P.; Ronkainen, Jussi G.; Liimatainen, Maarit; Hu, Yuntao; Nykänen, Hannu; Biasi, Christina; Maljanen, Marja (Springer Nature, 2021)
Nitrous acid (HONO) photolysis produces hydroxyl radicals—a key atmospheric oxidant. Soils are strong HONO emitters, yet HONO production pathways in soils and their relative contributions are poorly constrained. Here, we conduct 15N tracer experiments and isotope pool dilution assays on two types of agricultural soils in Finland to determine HONO emission fluxes and pathways. We show that microbial processes are more important than abiotic processes for HONO emissions. Microbial nitrate reduction (denitrification) considerably exceeded ammonium oxidation as a source of nitrite—a central nitrogen pool connected with HONO emissions. Denitrification contributed 97% and 62% of total HONO fluxes in low and high organic matter soil, respectively. Microbial ammonium oxidation only produced HONO in high organic matter soil (10%). Our findings indicate that microbial nitrate reduction is an important HONO production pathway in aerobic soils, suggesting that terrestrial ecosystems favouring it could be HONO emission hotspots, thereby influencing atmospheric chemistry.
Keywords: denitrification; agricultural soils; nitrous acid